Review of Shooting Terror. Terrorism in Hindi Films. By Meenakshi Bharat. - Sikorska, Liliana (Studia Anglica Posnaniensia, 2023)
Review of Shooting Terror. Terrorism in Hindi Films. By Meenakshi Bharat.